Air Quality Deep Dive - Bulgaria, Croatia, Poland and Romania : Sustainable Cities Implementation Framework - World Bank (Washington, DC, 2022)
The World Bank is developing a Sustainable Cities Implementation Framework for Europe and Central Asia to inform World Bank and other development partners’ ongoing support to national and sub-national authorities in pursuit of Sustainable Cities. As part of this work, preliminary assessments were conducted in four countries (Bulgaria, Croatia, Poland and Romania), which identified the need for deep dive analytics on three topics (Air Quality, Spatial Form and Solid Waste Management). This report explores air quality challenges in urban areas, focusing on existing data, identifying contributing factors to poor air quality, and providing recommendations (implementation support areas) to improve air quality in Bulgaria, Croatia, Poland and Romania. Air pollution has a major impact on the sustainability of an urban area. It is a significant cause of premature death and morbidity, representing the single, largest environmental health risk in Europe. People in the larger cities tend to be exposed to higher levels of nitrogen dioxide due to emissions from road traffic. In central and eastern Europe, air quality is poor in many areas, especially in urban settings, and the burning of solid fuels for domestic heating and in industry results in public exposure to the highest concentrations of particulate matter and polycyclic hydrocarbons.